Distributed Precoder Design With Direct-Link Channel Information for Distributed Antenna Systems - Joung, Jingon; Nguyen, Hieu Duy; Sun, Sumei (IEEE transactions on vehicular technology, 2018)
In this study, we investigate distributed antenna systems (DASs) with partial channel state information (CSI). In the DAS considered here, one control unit coordinates multiple baseband units (BBUs), and each BBU with multiple distributed antennas (DAs) knows only the direct channels from its DAs to its associated users and supports them simultaneously. For fairness among users, a distributed precoder structure is designed to maximize the upper bound of the minimum user rate, under the assumption that the direct channel dominates the intra-BBU interfering links. We then propose a distributed general precoder that allows multiple BBUs to serve multiple users simultaneously. Numerical results verify that, in terms of the minimum and average achievable rates, the proposed scheme significantly outperforms an existing scheme in which each BBU supports a single user. The results also demonstrate that the proposed scheme is comparable to a full-CSI based scheme.